Apuleyo or the magic of love: Archetypes and mythical imaginary for a fairy tale and its Contemporary interdisciplinary reception - Escobar Borrego, Francisco Javier (Amaltea. Revista de Mitocrítica, 2018)
This article offers an interdisciplinary and diachronic study of the main archetypes and mythemes that articulate the story of Psyche and Cupid, inserted in the Golden Ass of Apuleyo, author accused of magical arts. To do so, they are analyzed from Classical antiquity and later periods, as a protohistory, until their Contemporary reception. The disciplines taken into account are Hispanic literature, with attention to the European context, anthropology, psychology, fine arts and music. In this intersection of codes stands out, in short, the feminine archetype of Psyche (Alma) and its symbolic dimension of butterfly.
Keywords: Apuleius; Golden ass; Psyche; Cupid; myth; fairy tale; magic; fantasy